2015
DOI: 10.7232/iems.2015.14.1.094
|View full text |Cite
|
Sign up to set email alerts
|

Individual Control over the Physical Work Environment to Affect Creativity

Abstract: The purpose of this paper is to provide a review of the background information regarding to the impact of personal control over the physical work environment on satisfaction with work environment and creativity at work. Today creativity has a significant and special place in business especially in innovative organizations which need creative people to generate new, and useful ideas for produce new products, services, work methods, systems etc. Moreover the design and appearance of workspace and individual abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 74 publications
(127 reference statements)
0
9
0
3
Order By: Relevance
“…Furthermore, it can influence individuals’ or groups’ ability to arrange and control their situation for continuity and coherence with the whole organization, such that physical space in the work environment can contribute to peoples’ and organizations’ competitive advantages. Thus, promoting individuals’ satisfaction and performance is possible, due to paying more attention to designing the workplace and facilitating the work environment to have more control over their workspace (Samani, Rasid, & bt Sofian, ). Figure shows the overall effect of the workplace, in terms of personal control over the workplace and distraction from the work environment, on individual satisfaction with workplace and performance, which comes from the review of prior studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Furthermore, it can influence individuals’ or groups’ ability to arrange and control their situation for continuity and coherence with the whole organization, such that physical space in the work environment can contribute to peoples’ and organizations’ competitive advantages. Thus, promoting individuals’ satisfaction and performance is possible, due to paying more attention to designing the workplace and facilitating the work environment to have more control over their workspace (Samani, Rasid, & bt Sofian, ). Figure shows the overall effect of the workplace, in terms of personal control over the workplace and distraction from the work environment, on individual satisfaction with workplace and performance, which comes from the review of prior studies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Different types of office layouts have different effects on employee relations and communications (Brennan, Chugh, & Kline, ; Hua, ). Although open‐plan designs have been found to enhance the social interactions that contribute to creativity (Amabile & Pillemer, 2012; Brachos, Kostopoulos, Soderquist, & Prastacos, 2007), they also decrease employees’ sense of personal control and increase the likelihood of distraction, which can affect individuals’ satisfaction with both their environment and outcomes (Hwang & Kim, ; Samani, Rasid, & Sofian, ). De Been and Beijer ( ) suggested that people working in open‐plan offices were less satisfied with the physical work environment (in terms of indoor climate) than people working in individual and shared‐room offices.…”
Section: A Closer Look At the Impact Of Office Design On Employee Outmentioning
confidence: 99%
“…Previous studies have shown that the perceived quality of the physical work environment influenced employees’ job satisfaction, psychological stress, attitudes, and overall performance (Carlopio, ; Davis, Leach, & Clegg, ; De Been & Beijer, ; George & Brief, ; Hua, Loftness, Heerwagen, & Powell, ; Huang, Robertson, & Chang, ; Hwang & Kim, ; Lee, ; McGuire & McLaren, ; O'Neill, ; Samani, Rasid, & Sofian, ; Sundstrom, Town, Rice, Osborn, & Brill, ; Thatcher & Milner, ; Vischer, ). Specifically, a high‐quality workplace helped generate positive emotions that enabled individuals to face challenging situations.…”
Section: A Closer Look At the Impact Of Office Design On Employee Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental satisfaction occurs in settings where individuals feel that their expectations and basic needs are being met (Lee, 2006). Employees within an organization typically need to adjust their own needs and requirements to the environmental features and ambient condition of the workplace in order to control the use of space and to create personal space that will enhance their productivity (Boerstra, Beuker, Loomans, & Hensen, 2013;Brager, Paliaga, & De Dear, 2004;Lee & Brand, 2010;Samani, Rasid, & Sofian, 2015a). Psychologists have generally found job satisfaction and positive organizational outcome to be the two main consequences of a suitable work environment.…”
Section: Introductionmentioning
confidence: 99%